Chromosomal copy number changes in patients with non-syndromic X linked mental retardation detected by array CGH. Issue 4 (16th September 2005) - Lugtenberg, D; de Brouwer, A P M; Kleefstra, T; Oudakker, A R; Frints, S G M; Schrander-Stumpel, C T R M; Fryns, J P; Jensen, L R; Chelly, J; Moraine, C; Turner, G; Veltman, J A; et al.
Abstract : Several studies have shown that array based comparative genomic hybridisation (CGH) is a powerful tool for the detection of copy number changes in the genome of individuals with a congenital disorder. In this study, 40 patients with non-specific X linked mental retardation were analysed with full coverage, X chromosomal, bacterial artificial chromosome arrays. Copy number changes were validated by multiplex ligation dependent probe amplification as a fast method to detect duplications and deletions in patient and control DNA. This approach has the capacity to detect copy number changes as small as 100 kb. We identified three causative duplications: one family with a 7 Mb duplication in Xp22.2 and two families with a 500 kb duplication in Xq28 encompassing the MECP2 gene. In addition, we detected four regions with copy number changes that were frequently identified in our group of patients and therefore most likely represent genomic polymorphisms. These results confirm the power of array CGH as a diagnostic tool, but also emphasise the necessity to perform proper validation experiments by an independent technique.